2013
DOI: 10.6026/97320630009929
|View full text |Cite
|
Sign up to set email alerts
|

A Structured-based Model for the Decreased Activity of Ala222Val and Glu429Ala Methylenetetrahydrofolate Reductase (MTHFR) Mutants

Abstract: The structure of human Methylenetetrahydrofolate Reductase (MTHFR) is not known either by NMR or by X-ray methods. Phosphorylation seems to play an important role in the functioning of this flavoprotein. MTHFR catalyzes an irreversible reaction in homocysteine metabolism. Phosphorylation decreases the activity of MTHFR by enhancing the sensitivity of the enzyme to SAdenosylmethione. Two common polymorphisms in MTHFR, Ala222Val and Glu429Ala, can result in a number of vascular diseases. Effects of the Glu429Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…46 The C677T SNP is located in the N-terminal catalytic domain and is responsible for the reduction of 75% of the enzyme activity in homozygous individuals as demonstrated by in vivo assays in human lymphocytes, in vitro assays using recombinant proteins and by bioinformatics predictions. [46][47][48] The A1298C SNP is situated in the C-terminal catalytic domain binding S-adenosylmethionine (SAM), the allosteric inhibitor that negatively regulates MTHFR activity in response to methionine levels, and also acts as the main methyl donor for DNA methylation. 49 This SNP was associated with a moderate reduction of MTHFR activity (by 39% in human lymphocytes), however this was not confirmed by in vitro studies, suggesting in fact that it does not directly impact the catalytic activity of the enzyme, but rather the ability of SAM to exercise its regulatory function.…”
Section: Discussionmentioning
confidence: 99%
“…46 The C677T SNP is located in the N-terminal catalytic domain and is responsible for the reduction of 75% of the enzyme activity in homozygous individuals as demonstrated by in vivo assays in human lymphocytes, in vitro assays using recombinant proteins and by bioinformatics predictions. [46][47][48] The A1298C SNP is situated in the C-terminal catalytic domain binding S-adenosylmethionine (SAM), the allosteric inhibitor that negatively regulates MTHFR activity in response to methionine levels, and also acts as the main methyl donor for DNA methylation. 49 This SNP was associated with a moderate reduction of MTHFR activity (by 39% in human lymphocytes), however this was not confirmed by in vitro studies, suggesting in fact that it does not directly impact the catalytic activity of the enzyme, but rather the ability of SAM to exercise its regulatory function.…”
Section: Discussionmentioning
confidence: 99%
“…The MTHFR C677T mutation is located in the catalytic domain of the enzyme and causes an alanine-tovaline substitution at position 222 (27). A previous study demonstrated that this mutation results in a thermolabile enzyme; the homozygous mutation causes an approximately 70% decrease and the heterozygous mutation results in a 35% decrease in the mean MTHFR activity (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed the mutation of MTHFR C677T decreased the serum AST level (Table 2). MTHFR A1298C is located in the regulatory domain named NADPH and S-adenosylmethionine (SAM) binding site (27). The A1298C mutation does not result in synthesis of a thermolabile protein (30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Ala222Val substitution in human MTHFR affect the phosphorylation sites in the enzyme structure by affecting the FAD-binding sites. Phosphorylation may play an essential role in the function of wild-type enzyme (Shahzad et al, 2013). Karimian and Hosseinzadeh Colagar (2014) reported that Ala222Val changes physicochemical properties of MTHFR.…”
Section: Q5mentioning
confidence: 99%